Improving Indonesian Language Learning Outcomes Through The Problem Based Learning Model Assisted with Video Learning in Class III Students of Ngemplak Simongan 01 State Primary School - Intania, Belita Yoan; Ansori, Isa; Suryawati, Ani; Setianingsih, Rini Aris (Jurnal Ilmiah Profesi Pendidikan, 2024)
Improving Indonesian Language Learning Outcomes through Models Problem Based Learning Assisted with Learning Videos for Class III Students at Ngemplak Simongan 01 State Elementary School. This type of research is classroom action research which consists of planning, implementation, observation and reflection stages. Implemented in two cycles, each cycle consisting of two meetings. The subjects of this research were class III students at SD Negeri Ngemplak Simongan 01 with a total of 28 students. The research instruments used observation sheets, field notes, tests, interviews and documentation. The data analysis technique uses data analysis from observations of learning implementation and data analysis on student learning outcomes. The results of the research show that: 1) teacher skills increased, namely in cycle I with good criteria and cycle II very good, 2) student activity increased in cycle I obtained sufficient criteria, cycle II was good, 3) learning outcomes in prasikus percentage of completeness with grades the average was 55 and increased in cycle II to 85. Then the percentage of implementation of Indonesian language learning increased from 67.5% to 81%. Then, with the increase in Indonesian language learning outcomes, the percentage increased from 25% to 79%. The conclusion of this research is a modelproblem based learning (PBL) assisted by learning videos can improve the learning outcomes of Indonesian language lesson content for class III at SD Negeri Ngemplak Simongan 01 including teacher skills, student activities and learning outcomes. Suggestions for improving learning, teachers should develop students' courage and ability to ask questions and express opinions by providing motivation and stimulus to students in learning activities.